The clinical observation of human papillomavirus positive breast tumor - M. K. Ibragimova; M. M. Tsyganov; N. A. Tarabanovskaya; L. A. Tashireva; I. V. Deryusheva; V. M. Perelmuter; E. M. Slonimskaya; N. V. Litviakov (Бюллетень сибирской медицины)
In this manuscript, a unique case of HPV16-positive breast cancer is examined. The presence of HPV infection in the tumor is confirmed by two independent methods (PCR and immunohistochemistry). It is shown that in the presence of adverse factors of prognosis (lymphogenous metastasis, high level of Ki67 expression, presence of chromotrypsis in the tumor, and high level of genetic instability), a patient with a HPV-positive breast tumor has more than 8-year disease-free survival.